THE USE OF TERMS AND SENTENCES CONTAINING THE MEANING OF CRITICAL DISCOURSE BY OPINION LEADER IN LEGAL LANGUAGE IN THE CASE OF THE POLICY ON THE USE OF THE COVID-19 VACCINE - Achmad Nashrudin Priatna (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This article aims to discuss the discourse conveyed by the opinion leader regarding the policy on the use of the covid 19 vaccine. This article uses a qualitative method with critical discourse analysis and to access and retrieve data in the narrative displayed by online media using N Capture on the N Vivo 12 plus. The conclusion is that critical discourse by opinion leaders shows the existence of an ideology of interest, such as business vaccines or monopoly vaccines originating from one country, so the term "hammer and sickle vaccine" appears. There are manipulative deconstructions, such as the term “vaccine drama”. Although the social practices carried out by opinion leaders in the critical discourse, there are also constructive ones, such as support for domestically produced vaccines and free vaccines. Thus, the social practices carried out by opinion leaders are not completely destructive in dismantling the dominant discourse related to the Covid-19 vaccine. There are several policies that have the support of opinion leaders